Effect of Post-Activation Potentiation on Weightlifting Performance and Endocrinological Responses - Shyam Chavda; Angela Sorensen; James Vernau; Frank Hills; Chris Bishop; Anthony Nicholas Turner (Applied Sciences)
Purpose: This study examined the acute performance-enhancing effects and endocrinological responses of a supramaximal clean pull performed at 120% of clean and jerk, one repetition maximum, on clean performance. Methods: Eight (n = 8) ranked collegiate level weightlifters attended two days of testing in a randomised order. A control session was used to identify a baseline measure of kinetic and kinematic clean performance and endocrinological status following three cleans interspersed with one-minute recovery between repetitions. The experimental condition required participants to perform a single clean pull at 120% of clean and jerk, one repetition maximum, followed by three minutes recovery, prior to executing three cleans with one-minute recovery between repetitions. All cleans were performed on a dual force plate set up, synchronised with a 3D motion capture system to simultaneously record barbell and ground reaction force data. All endocrinological data were measured prior to the participant warming up and also following each testing protocol. Results: The results indicated that no significant differences were found between the control and PAP condition (p = 0.140–0.902); however, effect sizes from group analysis identified moderately negative to trivial effects across kinetic, kinematic and endocrinological variables (d = −0.30–0.14). Further analysis on an individual level demonstrated values, both negative and positive, ranging from extremely large (d = −4.10) to trivial (d = 0.04). Conclusions: The findings suggest a potentially negative affect of PAP on kinetic and kinematic measures of clean performance. However, individual responses varied, and thus some weightlifters may find this useful.